Polypharmacology of S-1117, an Fc-fused IgG-selective degrading enzyme, for chronic treatment of autoantibody-mediated diseases - Liliana M. Sanmarco; Alex Pellerin; Tobias Green; Agustin Plasencia; Jordan M. Anderson; Nam Le; Andita Newton; Jiyun Chen; Maria Cecilia Ramello; Ryan Peckner; Julia Manasson; Yi Xing; et al. (Proceedings of the National Academy of Sciences, 2026)
Antigen-specific immunoglobulin-G (IgG) antibodies cause or contribute to the pathogenesis of a wide spectrum of human diseases and conditions. Multiple therapeutic approaches have been developed, yet they are limited by variable safety and efficacy, patient inconvenience, and cost. IdeS, a cysteine protease derived from S. pyogenes , specifically cleaves IgG antibodies, representing a unique opportunity for the treatment of IgG-mediated diseases. However, clinical utilization of IdeS is limited by the immunogenic nature of bacterial proteases and short half-life. Using Seismic’s IMPACT platform, we engineered S-1117, an IgG cleaving enzyme fused to a human effectorless IgG1 Fc domain for an extended half-life. S-1117 is being developed to address the limitations of existing therapies in IgG-mediated diseases. In vitro and in vivo pharmacology studies demonstrate that S-1117 exhibits reduced B and T cell immunogenicity, a superior pharmacokinetic profile, and manufacturability and developability properties resembling those of monoclonal antibodies. S-1117 cleavage of IgG reduces circulating levels of IgG, including pathogenic IgG autoantibodies and IgG immune-complexes, and reduces IgG antibody effector functions, such as complement fixation, antibody-dependent cellular cytotoxicity, and antibody-dependent cell phagocytosis. The polypharmacology of S-1117 further extends to cleaving the antigen receptor on IgG-positive memory B cells, thereby modulating activation of memory B cells.